Metaverse in the Classroom: A Design-Based Study of Virtual Reality for Teaching Empathy and Collaboration Skills - Mardiati Mardiati (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. The integration of immersive technologies such as virtual reality (VR) in education has created new opportunities for enhancing students’ social-emotional learning. While traditional classrooms often face challenges in fostering empathy and collaboration, VR-based environments within the metaverse provide interactive and experiential learning spaces that allow students to engage with diverse perspectives and practice cooperative problem-solving. Purpose. This design-based study aimed to explore how VR-supported metaverse classrooms can be utilized to develop empathy and collaboration skills among secondary and university students. Specifically, the research examined how virtual role-playing scenarios and team-based tasks influence learners’ attitudes, behaviors, and social interactions. Method. The study involved three iterative design cycles conducted in metaverse learning environments, with participation from 152 students across two universities and one high school. Data were collected through pre- and post-intervention surveys, behavioral observations, and focus group interviews. The analysis combined quantitative measures of empathy and collaboration with qualitative insights into learners’ experiences. Results. The findings demonstrate that VR-enabled metaverse activities significantly enhanced students’ ability to empathize with others and engage in effective teamwork. Learners reported a greater sense of presence, increased willingness to adopt multiple perspectives, and improved conflict-resolution strategies during collaborative tasks. Iterative refinements across the design cycles further highlighted the importance of scaffolding, instructor facilitation, and culturally responsive content in achieving meaningful learning outcomes. Conclusion. This study provides empirical evidence supporting the potential of VR-based metaverse classrooms in fostering empathy and collaboration skills. The results suggest that immersive learning environments can complement conventional pedagogical practices, offering educators innovative tools to cultivate essential 21st-century competencies.